2020
DOI: 10.1128/mbio.02128-20
|View full text |Cite
|
Sign up to set email alerts
|

Network Rewiring: Physiological Consequences of Reciprocally Exchanging the Physical Locations and Growth-Phase-Dependent Expression Patterns of the Salmonella fis and dps Genes

Abstract: The Fis nucleoid-associated protein controls the expression of a large and diverse regulon of genes in Gram-negative bacteria. Fis production is normally maximal in bacteria during the early exponential phase of batch culture growth, becoming almost undetectable by the onset of stationary phase. We tested the effect on the Fis regulatory network in Salmonella of moving the complete fis gene from its usual location near the origin of chromosomal replication to the position normally occupied by the dps gene in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 99 publications
(133 reference statements)
1
30
0
Order By: Relevance
“…It is thus conceivable that the observed spatial patterns of regulons and couplons are selected to optimize the exposure of target genes to the gradients of diffusing regulators. Furthermore, recent observations that alterations of gene expression and phenotype can be induced by chromosomal position shift of a NAP gene, despite the maintenance of its natural expression pattern [105] and, that the effect of positional shift can be aggravated by altering the expression pattern of the NAP gene [107], support the proposal that the physical structure of chromosome is optimized by direct regulatory interactions involving the NAPs and other DNA structuring proteins [133]. In this respect it is relevant, that the NAPs can distinctly modulate the chromosomal regional dynamics by inducing transient domain boundaries in the genome [134,135].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus conceivable that the observed spatial patterns of regulons and couplons are selected to optimize the exposure of target genes to the gradients of diffusing regulators. Furthermore, recent observations that alterations of gene expression and phenotype can be induced by chromosomal position shift of a NAP gene, despite the maintenance of its natural expression pattern [105] and, that the effect of positional shift can be aggravated by altering the expression pattern of the NAP gene [107], support the proposal that the physical structure of chromosome is optimized by direct regulatory interactions involving the NAPs and other DNA structuring proteins [133]. In this respect it is relevant, that the NAPs can distinctly modulate the chromosomal regional dynamics by inducing transient domain boundaries in the genome [134,135].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the existence of this superhelicity gradient could not be experimentally demonstrated. However, the importance of gene order along the chromosomal OriC-Ter axis has been supported by genetic studies demonstrating that chromosomal position shifts of regulatory genes lead to rewiring of the genetic network as well as alterations of both the growth phase-dependent DNA supercoil dynamics and the bacterial phenotype [105][106][107]. Furthermore, the chromosomal gene order appears to underlie the spatial organization of function in genome.…”
Section: Spatiotemporal Organization Of Transcription In Genomementioning
confidence: 99%
“…That these enzymes exert opposite effects on DNA supercoiling precludes a straightforward relationship between DNA supercoiling and Mg 2+ concentration. In S. Typhimurium , Mg 2+ starvation causes DNA relaxation, 55,121 which may reflect that DNA gyrase is more sensitive to Mg 2+ availability than Topo I. Curiously, excess Mg 2+ also causes relaxation in S. Typhimurium 55 .…”
Section: Post‐translational Factors Act On Topoisomerases To Alter Dna Supercoilingmentioning
confidence: 99%
“…Several studies have shown that gene position on the chromosome is physiologically significant in bacteria (Bogue et al., 2020 ; Bryant et al., 2014 ; Gerganova et al., 2015 ; Scholz et al., 2019 ). For example, moving the gene that encodes the nucleoid‐associated protein FIS (Factor for Inversion Stimulation) from its native position, proximal to the origin of chromosome replication in E .…”
Section: Introductionmentioning
confidence: 99%